Relationship between organization's Corporate Social Responsibility (CSR) programs and employees' organizational commitment and psychological well-being / Nor Iziana Azlin Ahmad Azmi - Ahmad Azmi, Nor Iziana Azlin (2018)
The aim of this study was to investigate the relationship between Organization's CSR Programs and Employees' Organizational Commitment and Psychological Well¬ Being. 246 employees Standard Chartered Headquarter in Kuala Lumpur whose age range from 23 to 50 years participated in this study. Self administrated questionnaire was used to collect the information on demographic, organization's CSR programs, employees' organizational commitment and psychological well-being. Both descriptive and inferential statistic were applied to analyze the data collected. Pearson correlation coefficient was used to examine the relationship between organization's CSR programs and employees' organizational commitment. Similar inferential statistic also was applied to seek the relationship between organization's CSR programs and psychological well-being. The results yielded that, relationship between organization's CSR programs and employees' organizational commitment showed a significant relationship with low weak correlation (r=0.169, p=0.008). Similarly with organization's CSR programs and psychological well-being, the correlation also showed a low weak correlation (r=0.235, p=0.00 1).